Cyclodextrin inclusion complexes loaded in Particles As Drug Carrier Systems - Fraceto, Leonardo Fernandes [UNESP]; Grillo, Renato [UNESP]; Sobarzo-Sánchez, Eduardo (Bentham Science Publishers, 2014)
This mini-review paper does not consider classical work concerning the formation of inclusion complexes between pharmaceuticals and cyclodextrins. Instead, it highlights recent reports concerning the association of these host:guest systems with other carrier systems such as liposomes and nanoparticles showing the state of art of this subject with examples of developed systems and the advantages of these strategy in order to be potential systems as drug carriers. © 2014 Bentham Science Publishers.
Keywords: Cyclodextrin; Drug delivery; Liposome; Nanoparticle